2018
DOI: 10.1111/all.13619
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction, mucin, and inflammasome‐related molecules are differentially expressed in eosinophilic, mixed, and neutrophilic experimental asthma in mice

Abstract: Background: Asthma is a chronic respiratory disease with marked clinical and pathophysiological heterogeneity. Specific pathways are thought to be involved in the pathomechanisms of different inflammatory phenotypes of asthma; however, direct in vivo comparison has not been performed. Methods:We developed mouse models representing three different phenotypes of allergic airway inflammation-eosinophilic, mixed, and neutrophilic asthma via different methods of house dust mite sensitization and challenge. Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 53 publications
(70 reference statements)
7
131
0
Order By: Relevance
“…However, often endotypes can co-exist and/or include other mixed processes, which cannot be easily categorized (Kuo et al, 2017;Agache and Akdis, 2016;Cosío et al, 2017). Less well-defined forms of asthma, situated between clinical phenotypes and molecular endotypes, include inflammatory phenotypes of eosinophilic, neutrophilic, mixed, and paucigranulocytic asthma (Wang et al, 2011;Tan et al, 2019). Type 2 asthma is usually observed in the clinic as earlyonset allergic asthma, late-onset eosinophilic asthma, or exercise-induced asthma (Fahy, 2015).…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, often endotypes can co-exist and/or include other mixed processes, which cannot be easily categorized (Kuo et al, 2017;Agache and Akdis, 2016;Cosío et al, 2017). Less well-defined forms of asthma, situated between clinical phenotypes and molecular endotypes, include inflammatory phenotypes of eosinophilic, neutrophilic, mixed, and paucigranulocytic asthma (Wang et al, 2011;Tan et al, 2019). Type 2 asthma is usually observed in the clinic as earlyonset allergic asthma, late-onset eosinophilic asthma, or exercise-induced asthma (Fahy, 2015).…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…Non-type 2 asthma, observed more often in obesity-related asthma, neutrophilic asthma, and paucigranulocytic asthma (Kuo et al, 2017;Cosío et al, 2017;Ray and Kolls, 2017), is usually connected with poor responsiveness to steroids and more severe phenotypes, even in childhood (Ramratnam et al, 2017). Nontype 2 inflammation is characterized by infiltration of Th1 and Th17 cells and neutrophils, the presence of type I interferons, NLRP3 inflammasome activation, and an IL-1b and IL-17 signature (Rossios et al, 2018;Kim et al, 2017;Tan et al, 2019). The effect of microbiota dysbiosis on asthma heterogeneity seems intuitive, but, until recently (Taylor et al, 2018;Boutin et al, 2017), lung and gut microbiome composition have not been addressed in (Turnbaugh et al, 2007), lungs were not sampled, partially due to the existing dogma at the time that lungs are sterile.…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…Consequently, epithelial dysregulation and mutations or polymorphisms of genes important for skin barrier, such as filaggrin, SPINK5, 1 and SERPINB7, have been linked to eczema development and also food allergy. [2][3][4][5][6] Recently, electrical impedance spectroscopy has shown promising results in rodents to measure skin barrier function. This is of relevance since it can be easily adapted for usage on humans.…”
Section: Food Allergy and Barrier Functionmentioning
confidence: 99%
“…Together, these results suggested that BLT1 and BLT2 contribute to IL-17 production and airway inflammation in neutrophil-dominant pulmonary inflammation. LTB 4 We observed that 5-/12-LO expression in the lungs and LTB 4 and 12(S)-HETE serum levels were elevated in LPS/OVA-induced pulmonary inflammation group (Figure 2A,B). Histology analysis showed that MK886 or baicalein reduced airway inflammation compared to F I G U R E 2 Upregulation of BLT2 ligands, LTB 4 and 12(S)-HETE, is associated with neutrophil-dominant airway inflammation and IL-17 production.…”
Section: Leukotriene B 4 Receptors Mediate the Production Of Il-17 Tmentioning
confidence: 83%
“…Recently, IL-17 was shown to be associated with severe neutrophilic asthma development and exacerbation, and IL-17 levels in serum and sputum were shown to increase with disease severity. 3,4 Meanwhile, a previous study demonstrated that leukotriene B4 (LTB 4 ) is present at higher concentrations in sputum of patients with severe asthma, who have relatively pronounced neutrophil influx, than in those with mild asthma. 5 Furthermore, LTB 4 receptors, BLT1 and BLT2, were suggested to contribute to the development of asthmatic airway inflammation.…”
Section: Leukotriene B 4 Receptors Mediate the Production Of Il-17 Tmentioning
confidence: 99%